The Wallstent: long‐term follow‐up of metal stent placement for the treatment of benign ureteroileal anastomotic strictures after Bricker urinary diversion. (27th July 2014) - Campschroer, Thijs; Lock, M.T.W. Tycho; Lo, Rob T.H.; Bosch, J.L.H. Ruud
<x xml:space="preserve">Abstract</x> Objective To evaluate the long‐term follow‐up (primary and secondary patency) of metal stent placement in benign ureteroileal anastomotic strictures after Bricker urinary diversion and to compare the failed treatment group with the group of successfully treated patients to search for predisposing factors of stent failure. Patients and Methods For patients treated since 1989 for benign ureteroileal strictures after Bricker urinary diversion with end‐to‐side anastomosis, we retrospectively collected data on clinical history, stent placement, auxiliary measures and patency rates from a prospectively kept database. Results In all, 49 patients (mean age 64 years) underwent 56 metal stent procedures. Placement of the stent was possible in all patients. Stent patency without auxiliary treatment remained adequate in 23 cases (primary patency of 41.1%, mean follow‐up 37.7 months). A secondary treatment was successfully performed in 11 patients who had stent obstruction, mostly caused by hyperplastic reaction, encrustation, or migration of the stent. The secondary patency rate was 60.7% (mean follow‐up 55.8 months), comparable with patency rates of 36–100% described in literature with mostly small patient groups and much shorter follow‐up periods. Conclusion To the best of our knowledge we report the largest series of metal stenting in benign ureteroileal anastomotic strictures with the longest follow‐up. We show that placement of a metal stent can lead to a permanent de‐obstruction in approximately six out of 10 patients with preservation of renal function.